PENGARUH AUGMENTED REALITY MERKETING, ONLINE CUSTOMER REVIEW, DAN BRAND IMAGE TERHADAP MINAT BELI KOSMETIK MAYBELLINE DI PLATFORM SHOPEE: (STUDI PADA MAHASISWI FAKULTAS EKONOMI UNISDA) - Latifatul Ainiyah; Siti Shoimah; Miftahul Huda (J-MACC, 2025)
This study aims to analyze the influence of Augmented Reality Marketing, Online Customer Review, and Brand Image on purchase intention toward Maybelline cosmetics on the Shopee platform among students of the Faculty of Economics, UNISDA. This research employs a quantitative method with purposive sampling, involving 128 respondents. Data were analyzed using multiple linear regression. The results show that Augmented Reality Marketing has a negative and significant effect on purchase intention, indicating that the current AR feature does not provide a convincing experience for consumers. Online Customer Review has a positive and significant effect, demonstrating that consumer reviews are considered credible sources of information that strongly influence purchasing decisions. Brand Image has a positive and the most dominant effect on purchase intention, emphasizing that Maybelline’s strong brand reputation increases consumer confidence. Simultaneously, the three variables significantly affect purchase intention, with an Adjusted R-Square of 0.762. These findings highlight that brand image plays a central role in cosmetic purchasing behavior, while AR features require improvement to enhance the effectiveness of digital marketing strategies.